2010
DOI: 10.1371/journal.pone.0011298
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Plant DNA in the Bronchoalveolar Lavage of Patients with Ventilator-Associated Pneumonia

Abstract: BackgroundHospital-acquired infections such as nosocomial pneumonia are a serious cause of mortality for hospitalized patients, especially for those admitted to intensive care units (ICUs). Despite the number of the studies reported to date, the causative agents of pneumonia are not completely known. Herein, we found by molecular technique that vegetable and tobacco DNA may be detected in the bronchoalveolar lavage from patients with ventilator-associated pneumonia (VAP).Methodology/Principal FindingsIn the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Bronchoalveolar lavage was performed as previously described [27]. BAL samples were tested by RT-PCR, and standard cultures were performed to identify the bacteria and fungi present in the blood and BAL samples [28].…”
Section: Methodsmentioning
confidence: 99%
“…Bronchoalveolar lavage was performed as previously described [27]. BAL samples were tested by RT-PCR, and standard cultures were performed to identify the bacteria and fungi present in the blood and BAL samples [28].…”
Section: Methodsmentioning
confidence: 99%
“…With the progression of periodontal disease, the pathogenic bacteria in the oral cavity and oropharynx increases constantly, resulting in various types of pneumonia and respiratory infections as they arrive in the lower respiratory tract and lungs ( 8 ). Pneumonia-associated pathogens may be detected in the dental plaque of patients with pneumonia, and periodontal pathogens may be cultured from lung lavage fluid ( 9 ). Previous clinical studies ( 1 , 10 ) have indicated that periodontal infection may significantly increase the incidence of fatal pneumonia in patients on a ventilator, and there is an increased risk of mortality from respiratory diseases, such as pneumonia, in elderly patients with periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Later research confirmed the positive correlation between PMMoV virion content and some clinical signs, including fever and abnormal pain (Colson et al, 2010;Balique et al, 2015;Jiwaji et al, 2019) (Table 1). TMV is highly stable in tobacco products and was previously detected in the lungs of active or passive smokers and the bronchoalveolar lavage of intubated patients (Bousbia et al, 2010). Anti-PMMoV antibodies were identified more frequently in serum samples from patients with PMMoV than in control serum samples (Colson et al, 2010).…”
Section: Viral Phytopathogensmentioning
confidence: 92%